2016
DOI: 10.1038/srep24259
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of GnRHa Alone or in Combination with rhGH for the Treatment of Chinese Children with Central Precocious Puberty

Abstract: The addition of recombinant human growth hormone (rhGH) to GnRH agonist (GnRHa) to treat central precocious puberty (CPP) is controversial. We systemically reviewed and evaluated the efficacy and safety of the rhGH and GnRHa adjunctive therapy in Chinese children with CPP and assessed the influence of age and therapy duration on the efficacy of the combined treatment. A total of 464 patients were included from 14 studies. Compared with baseline, administration of GnRHa plus rhGH led to a significant increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…In addition to its inclusion of a total of 1,268 girls, another strength of this NMA was the specific inclusion criteria, complete search strategy, and eligibility assessed independently by two reviewers. Thirdly, Wang et al's (17) meta-analysis only analyzed 3 outcome measurements (height, PAH, and height standard deviation for bone age) with a total of 464 Chinese patients included from 14 studies, and Li et al's (18) meta-analysis included 8 studies with 309 girls and analyzed 2 endpoints (final height and standard deviation scores for final height). To provide a more complete clinical reference, we included 22 studies with 1,268 patients and 6 endpoints into analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to its inclusion of a total of 1,268 girls, another strength of this NMA was the specific inclusion criteria, complete search strategy, and eligibility assessed independently by two reviewers. Thirdly, Wang et al's (17) meta-analysis only analyzed 3 outcome measurements (height, PAH, and height standard deviation for bone age) with a total of 464 Chinese patients included from 14 studies, and Li et al's (18) meta-analysis included 8 studies with 309 girls and analyzed 2 endpoints (final height and standard deviation scores for final height). To provide a more complete clinical reference, we included 22 studies with 1,268 patients and 6 endpoints into analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients, the growth velocity decrease was so marked that predicted adult height (PAH) was impaired (16). Wang's meta-analysis included 14 studies composed of 7 observational studies and 7 case-control studies with a total of 464 Chinese patients (17). This study demonstrated that compared with GnRHa alone therapy, the addition of growth hormone (GH) to GnRHa treatment led to a marked increase in PAH, height, and height standard deviation for bone age, corresponding to a weighted mean difference (95% confidence interval [CI]) of 3.76 (3.19, 4.34) cm, 3.56 (2.54, 4.57) cm, and 0.56 (0.43, 0.69) cm, respectively (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results demonstrate that in prepubertal male rats, rhGH accelerated the functional maturation of Leydig cells and increased testosterone synthesis, contributing to an early onset of puberty. In rhGH therapy for human children with short stature, effective dosages of rhGH are 0.08–0.13 IU/kg/d [ 24 25 ]. In peripubertal rat model study, administration of rhGH at 2–11 IU/kg/d increased body growth [ 18 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a low growth velocity or no improvement in PAH during GnRHa benefitted most from the combination therapy ( 89 ) (LoE 2). A systematic review and meta-analysis reported an increase of PAH of 6.5 cm in CPP when treated with rhGH plus GnRHa, especially in those starting treatment before 10 years old, or with treatment lasting more than 12 months ( 90 ). Compared to GnRHa alone, the combined treatment showed a 3.7 cm higher PAH (LoE2).…”
Section: The Effect and Safety Of A Gnrh Analogue In Children With A Low Predicted Adult Heightmentioning
confidence: 99%